Giant right coronary artery aneurysm mimicking a right intra-ventricular mass: a case report - Teng, Peng (J Cardiothorac Surg, 2020)
BACKGROUND: Coronary artery aneurysm is a rare condition which constitutes a small proportion of coronary artery disease. Such condition mimicking an intra-cardiac mass is extremely rare and poorly understood. CASE PRESENTATION: We present an unusual case of a 53-year-old female with decreased exercise tolerance and lower extremity edema for 3 months. The echocardiography showed moderate tricuspid regurgitation and a right intra-ventricular mass below the tricuspid valve. No ventricular wall akinesia or ST segment change was found on echocardiography or electrocardiogram. Coronary computed tomographic angiography confirmed the diagnosis of intra-ventricular mass with feeding vessel originated from the right coronary artery. The patient was scheduled for tumor resection, and the mass turned out to be a thrombosed giant right coronary artery aneurysm. The patient received successful aneurysm resection and had an uneventful postoperative recovery. Unfortunately, a fistula between right coronary artery and right ventricle was detected on follow-up three months later by echocardiography. CONCLUSIONS: Coronary artery aneurysms presenting as intra-cardiac masses are extremely rare. Comprehensive preoperative evaluation is highly recommended because the surgical strategies for tumor and aneurysm are completely different. Aneurysm resection with bypass surgery is preferred rather than aneurysm repair. To our best knowledge, coronary artery aneurysms presenting as intra-ventricular masses have seldom been reported.